Act of March 23, 1935, ch. 172, §§ 1-4, Wash. Sess. Laws 599, 599. - (:unkn) unknown (My University, 1935)
'Short Firearm' as used in this act means any firearm with a barrel less than twelve (12) inches in length.If any person shall commit or attempt to commit a crime of violence when armed with a pistol, he may in addition to the punishment provided for the crime, be punished also as provided by this act.No person who has been convicted in this state or elsewhere of a crime of violence, shall own a pistol or have one in his possession or under his control."
Keywords: CARRY - INTENT TO COMMIT CRIME; DEFINITIONS; POSSESSION - DANGEROUS PERSONS